Los espacios públicos de la literatura contemporánea - Lionel Ruffel (Cuadernos LIRICO)
This article aims at criticizing Habermas’ notion of “public sphere”, a concept which, since its origins, has been closely linked with literature. The public sphere is described as an idealization in which the public of literature is defined as the result of a triple suppression (that of body, sound, and space). This representation does not describe accurately the contemporary practices, among which literary performances, public readings and non-print publications are increasingly taking centre stage.